Kesehatan Jiwa Individu di Masyarakat Pasca Isolasi di Fasilitas Isolasi Provinsi Riau - Deva Lestiarma S; Fathra Annis Nauli; Widia Lestari (STIKes Payung Negeri Pekanbaru, 2022)
Backgraound : The COVID-19 pandemic has resulted in changes in the process of life that can cause mental health problems. Especially individuals who had been in isolation COVID-19, individuals must be limited in their interactions and activities during isolation which causes a change in their situation afterwards. The purpose of this research is to get an overview of the mental health of individuals when they return to the community after isolation due to COVID-19. Methods : This research used a descriptive survey research design. The research sample was 100 respondents who were taken based on inclusion criteria using the snowball sampling technique. Result : The results showed 33 people (33%) had mental health problems. With the most complaints were PTSD symptoms(11%), the other complaints were psychologicalproblems (2%), psychotic symptoms (2%), and there was no indication of the use of addictive substances, but there were individuals who experience more than one mental health problem, the most (8%) experiencing psychological problems, psychotic symptoms and PTSD symptoms,then a psychological problems and PTSD symptoms (5%), psychotic symptoms and PTSD symptoms (4%), psychological and psychotic symptoms (1%). Conclusion : There needs to be further handling of individual mental health conditions after isolation due to COVID-19.